Análisis del segundo postulado de la teoría relativista - Sierra Pareja, Andrés Yesid (Revista Científica, 2011)
In the teaching of the relativity theory have shown some difficulties in understanding the second postulate by students, which hampers the proper development in the teaching of the relativity theory its entirety, therefore students only have limited to handle the mathematics, the theory`s omitting the conceptual part. Therefore, for the development of this work will analyze the second postulate of relativity from different points of view in the literature and its various presentations, looking at the role played by the postulate in relativity theory. To meet the objective of the work will be selected and examined books and articles to disclose the relativistic theory from the texts of teaching physics to high school levels and university, historical and philosophical books, factual texts of theory and introductory.